Foreign banks in emerging market crises: Evidence from Malaysia - Detragiache, Enrica; Gupta, Poonam (Journal of Financial Stability, 2006)
This paper compares performance of domestic and foreign banks in Malaysia during the Asian crisis. We find that foreign banks were not a homogeneous group: while banks with a stronger regional focus suffered from the crisis as much as domestic banks, foreign banks not focused on Asia performed significantly better. The key difference appears to be exposure to sectors hurt by the bursting of the asset price bubble. Availability of support from parent banks, likelihood of being bailed out, or political connections do not seem to explain the differences. Theories of managerial herding may explain why non-regional foreign banks were not caught in the financial bubble.